Efficacy of transversus abdominis plane block for gastric surgery: a meta-analysis - Hao Zhang; Hong Pan; Xiaodong Chen (BMC Anesthesiology)
Abstract Background Multimodal analgesia is an important component of Enhanced Recovery After Surgery (ERAS). Transversus abdominis plane (TAP) block helps achieve this pain management in various types of surgeries. To evaluate the efficacy of TAP block versus non-TAP approaches for postoperative pain management and recovery after gastric surgery. Methods A systematic literature search across four databases (Cochrane, Embase, Web of Science, PubMed) until February 2024 identified relevant randomized controlled trials (RCTs) evaluating TAP block in gastric surgery. Two independent reviewers screened studies, extracted data, and assessed analyses. Primary outcome: postoperative pain scores. Secondary outcomes: postoperative opioid consumption, hospital stay, time to ambulation, and time to flatus. Results Twelve RCTs involving 841 participants were included. Compared to non-TAP, the TAP group demonstrated significantly lower visual analog scale (VAS) pain scores at 1, 3, 6, 12, 24, and 48 h postoperatively (WMD range: -0.62 to -0.97). Time to first ambulation (SMD − 0.46; 95% CI: -0.92, 0.00) and first flatus (WMD − 5.17; 95% CI: -8.58, -1.77) were shorter in the TAP group. Postoperative opioid consumption was reduced with TAP (WMD − 1.89; 95% CI: -2.41, -1.37), with no difference in hospital stay between groups. Conclusion TAP block effectively relieves pain after gastric surgery, decreases postoperative morphine requirements, and modestly shortens bed rest duration while promoting intestinal function recovery. However, it does not significantly affect the overall hospital length of stay.